Pelatihan Perilaku Organisasional Untuk Meningkatkan Kualitas Pembelajaran Bagi Guru Sekolah Menengah Kejuruan Yadika Bangil - Desi Tri Kurniawati; Noermijati; Annisa Aulia Zahra (Jurnal Pemberdayaan Masyarakat, 2025)
Organizational behavior training constitutes one of the pivotal approaches in enhancing the quality of learning for Vocational High School (SMK) teachers. The primary issue identified was the insufficient understanding among teachers regarding the significance of organizational behavior in creating an effective learning environment. Through this training, teachers are equipped to comprehend group dynamics, effective communication, and leadership that can influence the classroom learning atmosphere. Consequently, organizational behavior training for SMK teachers represents a crucial step in efforts to improve learning quality. This training aims to enhance teachers' organizational behavioral competencies, thereby improving learning quality. This Community Service activity for 2025 is designed to enhance organizational behavior understanding among teachers at SMK Yadika Bangil Pasuruan, enabling material delivery to be conducted in a more structured manner and relevant to industrial needs. The implementation methodology in this Community Service activity comprises material presentation methods and practical/mentoring approaches. The outcomes of this service include enhanced teacher capacity in making appropriate learning decisions based on student needs, as well as promoting the creation of more effective, contextual teaching and learning processes oriented toward the work readiness of SMK Yadika Bangil graduates. Consequently, an improvement in learning quality within the vocational school environment is anticipated.